2012
DOI: 10.1128/jb.01173-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Pseudomonas sp. Strain Ag1, Isolated from the Midgut of the Malaria Mosquito Anopheles gambiae

Abstract: A Pseudomonas sp. bacterium was isolated from the midguts of Anopheles gambiae mosquitoes. Here we present the annotated Pseudomonas sp. draft genome sequence as a contribution to the efforts of characterization of the mosquito gut microbiome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…This is due to genome rearrangement, probably caused by IS3-family transposases (PSF113_1803-1804 and PSF113_4042-4043). Examination of other P. fluorescens genomes indicated that the genes invG , iagB and pseudogene related to hilA are present at the same chromosomal location in strains PAMC 25886 [66], Ag1 [67], 14–3 [68], WH6 [69], SBW25 [18], R81 [70], A506, BG33R, SS101 [20], NZ007, NZ052 and PMS117. Interestingly all these strains belong to subgroup V of the P. fluorescens group, which suggest that the SPI-1 cluster was lost before speciation of this sub-clade.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to genome rearrangement, probably caused by IS3-family transposases (PSF113_1803-1804 and PSF113_4042-4043). Examination of other P. fluorescens genomes indicated that the genes invG , iagB and pseudogene related to hilA are present at the same chromosomal location in strains PAMC 25886 [66], Ag1 [67], 14–3 [68], WH6 [69], SBW25 [18], R81 [70], A506, BG33R, SS101 [20], NZ007, NZ052 and PMS117. Interestingly all these strains belong to subgroup V of the P. fluorescens group, which suggest that the SPI-1 cluster was lost before speciation of this sub-clade.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the genomes of several mosquito derived bacterial strains have been sequences, including Asaia sp., Elizabethkingia anophelis , Enterobacter sp., Pseudomonas sp., Serratia sp., Stenotrophomonas maltophila , and Staphylococcus hominis 55565758596061. These genome data allow one to analyse the microbial genetic repertoire that may be associated with symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…This genomic organization appears to be conserved in the genomic sequences of a number of other isolates, mostly originating from plant or soil environments: P. fluorescens strains A506, Q2‐87, SS101, SBW25 (Loper et al ., ), BBc6R8 (Deveau et al ., ), F113 (Redondo‐Nieto et al ., ) and Pf29Arp (Marchi et al ., ), P. poae RE*1‐1‐14 (Müller et al ., ), P. putida W619 (Wu et al ., ), and Pseudomonas spp. Ag1 (Alvarez et al ., ), GM60, GM67 (Brown et al ., ), TKP (Ohtsubo et al ., ) and CF150 (McTee et al ., ).…”
Section: Tailocins: Phage Tail‐like Bacteriocinsmentioning
confidence: 99%